Cross-Generational Effects and Non-random Developmental Response to Temperature Variation in Paramecium - Hagen, Rebecca; Vitali, Valerio; Catania, Francesco (Frontiers in Cell and Developmental Biology, 2020)
Unicellular organisms such as ciliates are largely neglected in research on adaptive developmental plasticity, although their nuclear dualism offers ideal circumstances to study development outside an embryonic context. Here, we gain first insights into the ability of the ciliate Paramecium to develop potentially adaptive phenotypic changes in response to early-life adversity. We show that, upon exposure to unconventional culture temperatures, germline-to-soma differentiation gives rise to coordinated molecular changes that may help attune the number of functional gene copies to the new external conditions. The non-random somatic heterogeneity that developmental plasticity generates is largely epigenetically controlled, shaped by the parental experience, and may prompt a stress response. These findings establish Paramecium as a new model system to study the molecular basis and evolutionary significance of developmental plasticity. In echoing previous indications in mammals, they call for an incorporation of intergenerational effects in adaptation studies.